Adopting Industry 4.0 in Construction Industry - Mohammad Suferi, Nurul Syazwana; Rahman, Md Motiar (International Journal of Integrated Engineering, 2021)
Industries are often restrained to meet their aim in relation to productivity. This is due to the complexities and capabilities such as to cope with changing environment, for example technological developments and digitisation. Low productivity and ability for innovation are argued to be caused by the traditional nature of some industries. Hence, modern technology and/or concept like Industry 4.0 were developed for such industries to succeed in the modern world. This includes construction industry that demands for improvements to meet the clients’ needs such as faster production, increased quality and budget control. Thus, construction industry may benefit greatly by adapting to Industry 4.0 environment. This paper aims to address how construction industry and Industry 4.0 converge together, by focusing on the managerial efforts in construction industry: project management and strategic management. This paper is based on review of literature to examine the managerial efforts and relevant sets of critical success factors that have greater influence on construction industry, and establishing the importance of Industry 4.0 to construction industry. A framework has been conceptualised to show how construction industry links to Industry 4.0 by focusing on the managerial efforts. Future study in real life environment is required to support the components of the proposed framework, as well as to test and validate its application amongst practitioners.